COVID-19 crisis, work and employment: policy and research trends. (2nd October 2021) - Dhakal, Subas; Burgess, John; Connell, Julia
ABSTRACT: This special issue brings together a range of policy and research trends regarding COVID-19 Crisis, Work and Employment (CWE). Under the assumption that crises, disasters, emergencies are impediments to the broader Sustainable Development agenda, a rapid bibliometric analysis of CWE literature between 2020 and 2021 was also carried out as an antecedent to highlight emerging contexts and perspectives. As a collection, this special issue draws attention to empirical insights and practical cases from around the world for understanding the way various stakeholders responded to support the economy, employees and others during the COVID-19 crisis.